A Narrative Review Hospital Disaster Management as a Strategic Component of the National Emergency Response System: A Narrative Review - Wayan Dhea Agastya; Amalia Rahmadinie; Ayesha Jasmine Firdausi (Faculty of Medicine - Universitas Pembangunan Nasional Veteran Jawa Timur, 2026)
Hospitals constitute a critical pillar of national emergency response systems, particularly in disaster-prone regions. Beyond their clinical function, hospitals act as coordination hubs for medical response, triage, logistics, and intersectoral collaboration. This narrative review critically examines the strategic role of hospitals in disaster management across preparedness, mitigation, response, and recovery phases. Evidence from international guidelines, peer-reviewed studies, and Indonesian experiences indicates that structured hospital disaster management significantly improves operational resilience, continuity of essential services, and patient outcomes. Strengthening hospital disaster preparedness through standardized planning, regular simulations, and incident command systems is essential for enhancing health system resilience and reducing disaster-related morbidity and mortality.